PENGARUH SISTEM KOMPUTERISASI TERHADAP KINERJA KARYAWAN FRONT OFFICE DEPARTMENT DI PLANET HOLIDAY HOTEL & RESIDENCE BATAM - Muhammad Imron; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The development of technology has affected the service business to be able to compete in improving the quality service to the guest. The computerized system has been proven to help companies to launch operational work of its employees. This study aims to determine the significant effect of computerized system on the performance of front office department employees at Planet Holiday Hotel & Residence Batam, and to know the responses of front office department employees who use computerized system. The research method used in this research is quantitative descriptive approach. The data obtained from the results of questionnaires given to respondents and interview as many as 17 people with a census sampling technique which is front office department employees. The hotel uses a computerized system to help running smooth the operational work of its employees in serving guests due to the development and use of technology that is evenly to increase the competition with other hotels as well. From the results of the processed questionnaires, observations, and interviews it can be seen that there is a significant influence between computerized system on the performance of front office department employees at Planet Holiday Hotel & Residence Batam, with the influence of variables of 69.3%. As well as employee responses using computerized systems, prove that the system used is very helpful in completing the work so as to produce good performance.Keywords : Computerized System, Performance, Operational Work, Front Office, Hotel